(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article reviews Western perspectives — in a fruitful dialogue with non- Western perspectives — on the climate emergency and artistic experiences amid the ongoing debate about futures currently at stake in the climate crisis or climate emergency. Moving beyond the various ways of naming this crisis, we focus on how art can communicate, envision, and activate ways of inhabiting this problem, opening communities to an other-than-human coexistence and reconfiguring matters as we understand them in a geological, natural, or material sense. The analyses indicate that, instead of aiming at a singular solution, multiple exercises and imaginative and speculative avenues of narratives can tell different stories and envision alternative futures. If the climate crisis ignited in the Anthropocene is a shared crisis — both political and aesthetic — then art, inseparable from life and hence nature, holds a crucial role in nurturing care and the potency of imagining other possible worlds.